Internalisasi Hadis tentang Ketamakan dalam Pendidikan Karakter untuk Mencegah Hedonisme Peserta Didik - Muflih Naufal Irfan; Ilyas, Abustani; Yahya, Muhammad; Nursanti; Wafa, Itmamul (LPPAIK Universitas Muhammadiyah Bandung, 2025)
The phenomenon of sensual hedonism among students is increasingly worrisome as it negatively impacts morals, academic performance, and life balance. This paper aims to analyze the correlation between character education in Islam and the hedonism of students from the perspective of hadith, specifically Bukhari’s hadith number 6436 regarding greed. The research method used is qualitative, employing a literature review approach and thematic analysis of the hadith. The results of the study indicate that this hadith contains values of character education such as asceticism, self-control, and spiritual awareness that contrast with hedonistic values. By internalizing these values through character education, students can be directed to avoid a consumerist lifestyle and harmful social imaging. This study emphasizes that hadith-based character education can serve as a preventive solution to the deeply rooted hedonistic lifestyle in the modern era.